Effect Using Packaging Materials and Burning Time Madura Chicken Satay Based on Chemical and Organoleptic Quality - Megananda, Urania Noor Alina (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The aim of this research was to determine the effect of using packaging and burning time for Madura chicken satay based on chemical and organoleptic quality. The research method used a Completely Randomized Design (CRD) with 2 factors, factor A consisted of 2 treatments (A1 is 5 minutes burning and A2 is 10 minutes burning), and factor B consisted of 3 treatments (B0 without wrapping, B1 banana leaf wrapping, and B2 aluminum foil wrapping) which was repeated 3 times. The parameters were observed including PAH profile, water content, fat content, ash content, protein content, carbohydrate content by difference, and organoleptic. The data were analyzed by using analysis of variance (ANOVA) and continued with Duncan Multiple Range Test (DMRT). The results showed that the effect of using packaging materials and burning time for chicken satay Madura gave a very real or very significant difference (P<0.01). From this research, it can be concluded that burning chicken satay for 10 minutes with aluminum foil wrapping is the best and acceptable treatment because the results of all parameters are suitable with the Indonesian National Standard (SNI) for chemical quality.Keywords: Chicken satay, burning time, packaging, chemical, and organoleptic